Power on display : the politics of Shakespeare's major genres - Tennenhouse, Leonard, 1942- (History & politics ;, 2004)
First published in 1986. 'Impressively open to the complexity of cultural discourses, to the ways in which one discursive form may function as a screen for another above all to the political entailment of genre.' Stephen Greenblatt. What is the relation between literary and political power? How do the symbolic dimensions of social practice and the social dimensions of artistic practice relate to one another? Power on Display considers Shakespeare's progression from romantic comedies and history plays to tragedy and romance in the light of the general pr.